Pengaruh salinitas dan daya apung terhadap daya tetas telur ikan bandeng, Chanos-chanos - Sofyatuddin Karina; Rizwan R; Khairunnisak K (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. The objective of this research was to study the influence of salinity and buoyancy on hatchability of milkfish eggs (Chanos-chanos). The completely random design was used this study. Two factors i.e. salinity and buoyancy were tested where the salinity with three levels oncentration; 16, 23 and 30 ppt, while the buoyancy with three egg buoyancy categories i.e. floating, drifting and sinking with three replicates respectively. The result showed that the hatchability of floating eggs in tested salinities were 76,7% ; 78,75% ; 91,7%, for 16, 23 and 30 ppt, respectively. Then drifting eggs were 65,3%; 67,0%; 77,0% and sinking eggs were 54,0% ; 55,3% ; 65,0% for 16, 23 and 30 ppt, respectively. In generally, the hatchability was increased with increasing of salinity. In addition, the hatchability of the floating eggs was higher than the sinking eggs. Keyword: Salinity, buoyancy, hatchability, milkfish.